081 Lymphoma: a great imitator in neurology and its many faces. (29th July 2019) - Yeh, Wei Z; Muthusamy, Subramanian; McKelvie, Penny; Collins, Steven; French, Ann; Filshie, Robin; Reardon, Katrina
Abstract : Introduction: The label 'great imitator' refers to conditions which can cause varied manifestations and mimic diseases. Lymphoma is worthy of this title. We present three cases. Cases: 1: 66-year-old-man with progressive vertical diplopia and unsteady gait over four weeks. MRI brain and spine demonstrated a supratentorial para-falcine soft tissue lesion, mid-thoracic cord enhancement and right axillary mass. Serum ACE was elevated. Serum HIV serology was positive. Right axillary mass core biopsy diagnosed Burkitt lymphoma. 2: 50-year-old man with a 4-week history of constitutional symptoms on a background of ITP and splenomegaly. During admission he developed urinary retention, bilateral lower limb weakness and numbness and confusion. Infectious and vasculitic screens were unremarkable. CT chest, abdomen and pelvis demonstrated splenomegaly. CSF and bone marrow analyses were non-diagnostic. A random skin biopsy diagnosed intravascular lymphoma. 3: 65-year-old man with two weeks of headache and diplopia on a background of previously treated Burkitt lymphoma. CSF analysis showed 45×10 6 /L white cells and glucose < 0.6 mmol/L. Cytologic analysis was negative for malignancy. Bacterial culture and Cryptococcal antigen were negative. FDG-PET dramatically showed disseminated spinal and cranial leptomeningeal disease. MRI brain showed thin dural thickening correlating to area of increased uptake on PET. He was diagnosed with Burkitt lymphoma relapse and treated with chemotherapy and autologous stem cell transplant. Conclusion: The varied manifestations in our cases demonstrate the ability for lymphoma to mimic infective, inflammatory, granulomatous (including sarcoidosis) and neoplastic aetiologies. When the diagnosis is uncertain, the possibility of this great imitator should be considered.